Assessment of Thermal Oxidizer (Tox) Performance Efficiency - Nugroho, Budi Sulistiyo; Putri, Marsha Adinda (Indonesian Scientific Publication, 2024)
The use of a Thermal Oxidizer (TOX) aims to treat industrial waste gases by oxidizing harmful gases, such as sulphur dioxide (SO₂) and hydrogen sulphide (H₂S), at high temperatures. This study aims to evaluate the TOX operating conditions and analyze its efficiency in reducing harmful emissions released to the environment. Operating data is based on temperature, pressure, gas flow rate, and SO₂ concentration measurements from the Thermal Oxidizer (TOX). The measurement results show that the SO₂ emissions meet the government's standard setting below the maximum limit of 2,600 mg/Nm³. However, the actual TOX performance efficiency of 45.61% decreased compared to the initial design efficiency of 63.27%. This decrease was due to several factors, including reducing the hot oil flow rate and leakage in the chamber.